An Analysis of Human Development Determinants: A Case Study of Haryana: A Comparative Analysis of Human Development Determinants in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The prime aim of the study is to analyze and compare the Human Development Determinants in terms of Education, Health and Per Capita Income. Based on Agenda 2030, NITI Aayog has also started its own SDG (Sustainable Development Goals) Index to rank the various states and union territories as per their performance on the various parameters or set goals. The SDG India Index was developed in collaboration with the Ministry of Statistics Programme Implementation (MoSPI), Global Green Growth Institute and United Nations in India. These goals include 13 out of the 17 SDGs set by UN under Agenda 2030, and these all are targeting at uprooting of poverty and other deprivations for improving health and education, diminishing inequality, and accelerating the economic growth. The area of this study is all the districts in Haryana which include Ambala, Kurukshetra, Panchkula, Yamuna Nagar, Faridabad, Palwal, Nuh, Gurugram, Mahendragarh, Rewari, Fatehabad, Jind, Hisar, Sirsa, Jhajjar, CharkhiDadri, Rohtak, Sonipat, bhiwani, Karnal, Panipat, Kaithal. Haryana is ranked 22nd (with 76.64 literacy rate) among all the states and union territories in case of literacy rate. Overall literacy rate of Haryana is above the national literacy rate. Gurgaon district has the highest literacy rate, 84.70 in the state, followed by Faridabad, Panchkula, Ambala and Rohtak while Mewat is at the bottom with 54.08. In case of sex ratio Haryana is at 31st rank (with total of 879 females per 1000 males) among all states and union territories. The sex ratio of Sonipat and Gurugram is lowest at 853 and highest for Mewat at 906. In case of Income Per Capita, Haryana is ranked 13th with Rs. 199,612. Gurgaon is at the top of per capita income tally with PCI of Rs.4.46 lakh followed by Panipat with PCI of Rs. 1.64 lakh. Mewat has the lowest PCI of Rs. 45,934 followed by Mohindergarh with Rs. 54,835 and Palwal with Rs. 65,009.